2010
DOI: 10.2355/isijinternational.50.1965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al and P Additions on As-cast Austenite Grain Structure in 0.2 mass% Carbon Steel

Abstract: Fig. 13. The dependency of partition coefficient of P at liquidus temperature, k P , on Al concentration in the samples with different P concentrations obtained from CALPHAD method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Z badań przedstawionych w pracach [46][47][48] wynika, że wielkość ziarna austenitu pierwotnego zależy decydująco od wysokości temperatury, w której powstaje jednofazowa struktura γ. Punktem o najwyższej temperaturze, w którym powstaje jednofazowa struktura γ w stalach niestopowych i niskostopowych jest punkt d' na wykresie na rys. 4 i temu punktowi odpowiada największe ziarno austenitu pierwotnego.…”
Section: Związek Pierwotnej Struktury Krzepnięcia (Struktury Dendrytycznej) Z Ziarnową Strukturą Austenitu Pierwotnegounclassified
See 1 more Smart Citation
“…Z badań przedstawionych w pracach [46][47][48] wynika, że wielkość ziarna austenitu pierwotnego zależy decydująco od wysokości temperatury, w której powstaje jednofazowa struktura γ. Punktem o najwyższej temperaturze, w którym powstaje jednofazowa struktura γ w stalach niestopowych i niskostopowych jest punkt d' na wykresie na rys. 4 i temu punktowi odpowiada największe ziarno austenitu pierwotnego.…”
Section: Związek Pierwotnej Struktury Krzepnięcia (Struktury Dendrytycznej) Z Ziarnową Strukturą Austenitu Pierwotnegounclassified
“…4 i temu punktowi odpowiada największe ziarno austenitu pierwotnego. Do momentu, gdy w strukturze pozostaje druga faza, którą jest ferryt δ w stalach podperytektycznych i faza ciekła w stalach nadperytektycznych, wzrost ziarn austenitu jest hamowany [47,48]. Zwiększenie szybkości chłodzenia podczas krzepnięcia i bezpośrednio po zakrzepnięciu, obniżające temperaturę początku powstawania jednofazowej struktury austenitycznej, hamuje rozrost ziarn austenitu pierwotnego [46,49].…”
Section: Związek Pierwotnej Struktury Krzepnięcia (Struktury Dendrytycznej) Z Ziarnową Strukturą Austenitu Pierwotnegounclassified
“…SECOND-PHASE particles can provide a significant local pinning force on moving grain boundaries and moving interfaces and this effect can be, and is being, used to control the final grain size in polycrystalline metals exposed to a thermal treatment. [1][2][3][4] In microalloyed steels, carbide, nitride or carbonitride forming species, such as Nb or Ti, are widely used to assist microstructural control during thermomechanical processing by arresting static recrystallisation of austenite at low temperatures and inhibiting austenite grain coarsening. [5][6][7][8][9] A first theoretical analysis of the interaction of pre-existing (stationary) particles with migrating grain boundaries during recrystallization (i.e., conditions in which the same phase is present on both sides of the interface, but there is a large difference in dislocation density) was formulated by Zener and presented by Smith.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our recent investigation by means of permanent mold casting of 0.2 mass% carbon steel demonstrated that the addition of Al and/or P stabilizes the liquid or δ phase in low temperature region and such a stabilized phase hinders the migration of the FCG/CCG region boundary, thus yielding the fine γ grain structure consisting of FCG over the whole cast. 7,8) In addition to the liquid or δ phase stabilized at low temperatures, carbonitride particles are expected to be useful in preventing the migration of FCG/CCG region boundary. In this paper, we focus on effects of Nb addition on the as-cast γ grain structure in 0.2 mass% carbon steel which is prone to exhibit coarse γ grain structure because of its high Tγ .…”
Section: Introductionmentioning
confidence: 99%